Gas6/AXL pathway: immunological landscape and therapeutic potential - Zhai, Xiaoqian; Pu, Dan; Wang, Rulan; Zhang, Jiabi; Lin, Yiyun; Wang, Yuqing; Zhai, Ni; Peng, Xuan; Zhou, Qinghua; Li, Lu (Frontiers in Oncology, 2023)
Cancer is a disease with ecological and evolutionary unity, which seriously affects the survival and quality of human beings. Currently, many reports have suggested Gas6 plays an important role in cancer. Binding of gas6 to TAM receptors is associated with the carcinogenetic mechanisms of multiple malignancies, such as in breast cancer, chronic lymphocytic leukemia, non-small cell lung cancer, melanoma, prostate cancer, etc., and shortened overall survival. It is accepted that the Gas6/TAM pathway can promote the malignant transformation of various types of cancer cells. Gas6 has the highest affinity for Axl, an important member of the TAM receptor family. Knockdown of the TAM receptors Axl significantly affects cell cycle progression in tumor cells. Interestingly, Gas6 also has an essential function in the tumor microenvironment. The Gas6/AXL pathway regulates angiogenesis, immune-related molecular markers and the secretion of certain cytokines in the tumor microenvironment, and also modulates the functions of a variety of immune cells. In addition, evidence suggests that the Gas6/AXL pathway is involved in tumor therapy resistance. Recently, multiple studies have begun to explore in depth the importance of the Gas6/AXL pathway as a potential tumor therapeutic target as well as its broad promise in immunotherapy; therefore, a timely review of the characteristics of the Gas6/AXL pathway and its value in tumor treatment strategies is warranted. This comprehensive review assessed the roles of Gas6 and AXL receptors and their associated pathways in carcinogenesis and cancer progression, summarized the impact of Gas6/AXL on the tumor microenvironment, and highlighted the recent research progress on the relationship between Gas6/AXL and cancer drug resistance.